Modelling and Analysis of Bioretention Systems for Removal of Stormwater Pollutants - Nuwagaba, Emmanuel; Abdulkadir, Taofeeq Sholagberu; Agwe, Michael Tobby; Philip, Tibenderana; Ako, Terseer; Moses N., Twesigye-omwe (Kabale University, 2023)
A bio retention is the storm water best management practices (BMP) designed to capture and treat the runoff using the natural properties of soil and plants to remove contaminants. Storm water transports eroded soil, animal wastes, litter, salts, pesticides, fertilizers, oil and grease and other potential pollutants which flows directly into the streams and rivers. This damages the stream water quality and thereby causing a decline in aquatic biota. However, the selection of appropriate media structure, plants performance in bio retention system, and optimized design have not been adequately researched. More so, applicability of bio retention systems has not been introduced and implemented in Uganda. Thus, this study is aimed at investigating the efficiency of bio retention system in the removal of storm water pollutants using local plant, Dracaena, popularly known as Song of India Plants). Physical model of two Columns: B and C of 102 mm diameter were developed. Each of the Columns has four layers arranged as follows: Column B (Layer 1 for fine sand of 0.063 – 1.18 mm; Layer 2 for Coarse Sand of 1.18-4.75; Layer 3 for fine aggregate AASHTO M43, 4.75-9.5mm; and Layer 4 for Coarse aggregate >9.5mm), and Column C (Layer 1 for black soil with mulch and plants; fine Sand of 1.18-0.063; Layer 3 for fine aggregate AASHTO M43, 4.75-9.5mm; and Layer 4 for Coarse aggregate >9.5mm). The plants were introduced into columns C leaving out B as control experiment. Materials used in the media structure were analyzed to meet the standards according to the design manual. The quality parameters of raw storm water samples were determined before passing through the model and after passing through the model at different intervals i.e., at 0, 10, and 20 days after introducing the plants into the model. The parameters tested were Temperature, pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Total Coliforms (TC), Faecal Coliforms (FC), Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD) and Oil & Grease (OG)The results of the study showed that the bio retention model drastically improved storm water quality by reducing values of EC, TDS, TC, FC, TSS, BOD and OG as compared to the tested raw storm water samples. In Column C, the study showed 39.1% and 48.8 % reduction in TC and TSS concentrations respectively after 20 days of treatment as compared to 10 days. BOD of the storm water samples fell within the recommended standard after 20 days of treatment in Column C with considerable level of reduction in TC and FC by 68.9 % and 75.4 % respectively when compared to raw storm water sample. This study provides basis for developing bio retention system model with effectiveness of plants in the system. The study would be useful to the stakeholders in storm water management